Analysis of the Forward Kinematics and Workspace of 8-DOF Manipulator - Li Yawei; Huang Jinying (Jixie chuandong)
A study on the issue that the forward kinematics and workspace of a manipulator with 8--DOF is carried out.Firstly,according to the structural characteristics of the manipulator,the link coordinate system of manipulator are established by using D-H method,and its forward kinematics is obtained.Secondly,the simulation model of manipulator is set up by using the MATLAB Robotics Toolbox,and the correctness of the kinematics forward solution is testified.Finally,according to the position vector of the end actuator,the Monte Carlo method is applied to analyze the manipulator workspace,and the workspace range of the manipulator end actuator is acquired,and it is consistent with the design parameters of the manipulator.